2014
DOI: 10.3389/fphys.2014.00164
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and the epigenome

Abstract: Epigenetic mechanisms play a crucial role in regulating gene expression. The main mechanisms involve methylation of DNA and covalent modifications of histones by methylation, acetylation, phosphorylation, or ubiquitination. The complex interplay of different epigenetic mechanisms is mediated by enzymes acting in the nucleus. Modifications in DNA methylation are performed mainly by DNA methyltransferases (DNMTs) and ten-eleven translocation (TET) proteins, while a plethora of enzymes, such as histone acetyltran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
202
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(206 citation statements)
references
References 153 publications
(198 reference statements)
2
202
0
2
Order By: Relevance
“…Our studies were based on hypotheses of gestational programming, in this particular case claiming that low levels of 25(OH)D during periods of immune system maturation may cause long-term irreversible effects on immunological health [37]. It can be argued that one 25(OH)D measurement at a specific time-point (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies were based on hypotheses of gestational programming, in this particular case claiming that low levels of 25(OH)D during periods of immune system maturation may cause long-term irreversible effects on immunological health [37]. It can be argued that one 25(OH)D measurement at a specific time-point (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[93] The vitamin D receptor has a large CpG island in its promoter region so that it can be silenced by methylation, which is important because it interacts with coactivator and cosuppressor proteins that are in contact with chromatin modifiers and remodelers and it also has certain ligands that have DNA demethylating effects. [94] We can obtain convincing evidence of an anticancer role for vitamin D 3 in humans from a recent vitamin D 3 , calcium randomized clinical trial using supplements, [95] along with a pooled analysis of randomized trails, [96] and a prospective cohort study [97] because they showed significant reductions in their all-cancers risk. Intriguingly, Neanderthals gave some of the Europeans HPV16A, [98] so that this ancestry population had a "head start" for increasing their incidences of cancer over recent decades from indoor work and decreasing levels of vitamin D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D can activate or repress gene expression by recruiting histone acetyltransferases or histone deacetylases, respectively, to the vitamin D target genes. 79 In addition, Vitamin D can affect the expression of enzymes involved in histone demethylation. 79 These effects of vitamin D on histone modification have been demonstrated in several in vitro studies using cancer cell lines.…”
Section: Epigenetic Effects Of Environmental Risk Factors For Msmentioning
confidence: 99%
“…79 In addition, Vitamin D can affect the expression of enzymes involved in histone demethylation. 79 These effects of vitamin D on histone modification have been demonstrated in several in vitro studies using cancer cell lines. One study demonstrated that vitamin D suppresses the production of IL-17A, an inflammatory cytokine involved in MS exacerbation, from CD4 + T cells via the recruitment of histone deacetylase and a reduction in histone acetylation at the IL-17A promoter.…”
Section: Epigenetic Effects Of Environmental Risk Factors For Msmentioning
confidence: 99%